Some serum enzyme levels during pregnancy and postpartum in single and twin-bearing Akkaraman sheep - Gurdogan, F; Balikci, E; Yildiz, A (Polish Soc Veterinary Sciences Editorial Office, 2005)
The study was conducted to determine the changes in the blood serum ADA, AST, ALT, AP, LDH, CK, CKM and GGT values at 60, 100 and 150 days of pregnancy and day 45 of postpartum in single and twin-bearing Akkaraman sheep. Significant gradual decreases were determined for ADA (P < 0.001) and GGT (P < 0.05) enzymes during pregnancy in both groups while ADA (P < 0.001) and GGT (P < 0.05) values increased significantly on day 45 of postpartum. Significant increases (P < 0.01) were found for ALT and AST enzymes during pregnancy in both groups while ALT and AST levels decreased insignificantly on day 45 of postpartum. Serum AP, LDH, CK and CKM levels increased insignificantly during pregnancy and then decreased insignificantly on day 45 of postpartum. Serum ADA enzyme levels were lower (P < 0.01) during pregnancy in single-bearing ewes, compared with twin-bearing sheep.
Keywords: sheep; pregnancy